Construction site safety [electronic resource] : legal issues of liability for various parties - 379065 Shim, Mong Heng (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Pengurusan Kontrak Binaan)) - Universiti Teknologi Malaysia, 2006